Advances in wind turbine blade design and materials - Brøndsted, Povl; Nijssen, Rogier P. L.; Goutianos, Stergios (Woodhead Publishing in energy., 2023)
Advances in Wind Turbine Blade Design and Materials, Second Edition, builds on the thorough review of the design and functionality of wind turbine rotor blades and the requirements and challenges for composite materials used in both current and future designs of wind turbine blades.